Ethics and Personalized Training: An Experience with Cuban University Professors Training Administrative Personnel - Adilen Carpio-Camacho; María del Carmen Echevarría-Gómez; María de la Caridad Pérez-Martín; Osvaldo Romero-Romero (Universidad Nacional, Costa Rica, 2018)
The postulates of Víctor García Hoz, on teaching staff's behaviors characterized by preferences and attitudes, have been little analyzed in postgraduate teaching programs. The present article, based on a research project, shows an experience for strengthening the ethical formation of the Cuban university teaching staff that trains administrative personnel from the postulates of the referenced author, as a contribution to personalized education. The methodology developed from an interpretative perspective is applied to professors with the highest scientific and academic categories from the Faculties of Economics, Engineering and Humanities at the University of Sancti Spiritus. The experience is designed in three phases. The first one is descriptive, based on the selection and reading of documents and discussion groups, to know the essential elements of the professional ethics in the context of the university. The second one is empirical, where intervention is implemented to strengthen the ethical education of the teaching staff. The third phase is evaluative, based on the evaluation of the feasibility and validity of the intervention from questionnaires applied to experts, discussion groups, and participant observation. The results obtained confirmed the existence of an epistemological gap in the analysis of personalized teaching in the postgraduate program. The essential lies in the critical and reflexive comparison that the teaching staff, which trains administrative personnel, can make on how its ethical precepts are transformed, how it has an impact on its classroom practices, and how it has influence on responsible and integral actions of the people being trained, as well as on the shared responsibility of both the university and teachers.